Safe Implementation of Computerized Provider Order Entry for Adult Oncology - Martin, D.B.; Kaemingk, D.; Frieze, D.; Hendrie, P.; Payne, T.H. (Applied Clinical Informatics, 2015)
Background: Oncology has lagged in CPOE adoption due to the narrow therapeutic index of chemotherapy drugs, individualized dosing based on weight and height, regimen complexity, and workflows that include hard stops where safety checks are performed and documented.Objectives: We sought to establish CPOE for chemotherapy ordering and administration in an academic teaching institution using a commercially available CPOE system.Methods: A commercially available CPOE system was implemented throughout the hospital. A multidisciplinary team identified key safety gaps that required the development of a customized complex order display and a verification documentation workflow. Staff reported safety events were monitored for two years and compared to the year prior to go live.Results: A workflow was enabled to capture real-time provider verification status during the time from ordering to the administration of chemotherapy. A customized display system was embedded in the EMR to provide a single screen view of the relevant parameters of chemotherapy doses including current and previous patient measurements of height and weight, dose adjustments, provider verifications, prior chemotherapy regimens, and a synopsis of the standard regimen for reference. Our system went live with 127 chemotherapy plans and has been expanded to 189. Staff reported safety events decreased following implementation, particularly in the area of prescribing and transcribing by the second year of use.Conclusions: We observed reduced staff reported safety events following implementation of CPOE for inpatient chemotherapy using an electronic verification workflow and an embedded custom clinical decision support page. This implementation demonstrates that CPOE can be safely used for inpatient chemotherapy, even in an extremely complex environment.
Keywords: CPOE; chemotherapy; patient safety; transplant